Multi-channel third-harmonic generation via period 3D nonlinear photonic crystals - Yuming Yao; Tianxiang Xu; Ruwei Zhao; Xiaoying He; Yan Sheng (Results in Physics)
We report the cascaded third-harmonic generation (THG) via 3D quasi-phase matching (QPM) both theoretically and experimentally. A systematic demonstration of periodic 3D nonlinear photonic crystal (NPC) design for efficient THG is presented. A nonlinear photonic structure contains two subsections was fabricated by all-optical poling technique in an Sr0.61Ba0.39NbO3 crystal. The first segment is a 1D χ(2) grating for efficient collinear second-harmonic generation (SHG), while the second is a designed 3D NPC for THG. Effective collinear and non-collinear TH waves were realized, achieving maximum conversion efficiencies of 3.1 % for SHG and 8.4 × 10-3% for THG. Our findings deepen the understanding of cascaded THG in 3D NPCs and advance the development of multi-channel high-harmonic generation via high-dimensional QPM processes.